Performance Analysis of Low noise amplifier using Combline Bandpass Filter for X Band Applications - Lahsaini Mohammed; Toulali Islam; Zenkouar Lahbib (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This paper describes a procedure for designing broadband low noise amplifier for X-Band applications. The design and implementation is based on HEMT transistors AFP02N2-00 of Alpha Industries®. The matching circuit used for modeling the microwave amplifier is the quarter-wave transformers impedance matching technique associated to combline bandpass filter.  The proposed amplifier is implemented on a substrate of epoxy FR4 with a central frequency of 11GHz and a fractional bandwidth of 0.18% and is designed to be used in radar reception systems. The results show that the proposed LNA is unconditionally stable with a simulated gain of 20dB over the working frequency range of [9.5−12.5] GHz.